Corporate scandals in Malaysia: A political economy analysis of corporate governance reforms / Vighneswaran Vithiatharan - Vighneswaran, Vithiatharan (2015)
This study is about a paradox: Why is it, despite the extensive corporate governance reforms initiated by the Malaysian government after the 1997 Asian Financial Crisis (AFC), corporate scandals recur in the country? An assessment of this paradox inexorably converges attention on an important phenomenon – power and its concentration in a hegemonic state and its executive arm. This issue, a major gap in the literature about corporate governance, constitutes the focal point of this study. This study will adopt a multiple case study approach, examining four corporate scandals, which include Port Klang Free Zone Project, Sime Darby Berhad, National Feedlot Corporation and Tajuddin Ramli/Malaysian Airline System (MAS) Berhad. Utilizing Sherman’s (1978) cyclical scandal-reform logic model, this study will extract cogent thematic areas and analytical perspective of national corporate governance based on political economy and institutionalist thinking underlying the state’s failure or reluctance to mitigate the recurrence of corporate scandals in Malaysia.